Mechanical Properties and EMI-Shielding Efficiencies of Graphite and Iron(II) Oxide-Filled Polypropylene and Polyethylene-Based Polymer Composites - Kaftelen-Odabasi, Hulya; Khakberdiev, Elshod; Odabasi, Akin; Helhel, Selcuk (Springer International Publishing Ag, 2024)
In this study, polypropylene (PP), polyethylene (PE), PP/PE blends containing graphite (1-3 wt.%) and FeO (10-30 wt.%) fillers were prepared using a melt mixing method. The effects of graphite and iron oxide amount on the mechanical properties and electromagnetic interference (EMI) shielding efficiency in the frequency range of 8-12 GHz (X-band) were investigated. The tensile strength value of the PP/graphite/FeO (1:10) sample increased from 26.09 to 32.47 MPa with the increase of the graphite/FeO amount to 3:30 in wt.%. Maximum total shielding efficiencies of SET similar to 39.35 dB and 38.31 dB could be observed respectively with a corresponding frequency value of 12.2 GHz for PE and PP polymer mixture filled with 3 wt.% graphite and 30 wt.% FeO with a thickness of 4 mm. The results obtained from the EMI shielding measurements showed that the total EMI SE increased synergistically with increasing FeO/graphite hybrid filler amount for each polymer composition.
Characterization of Minerals, Metals, and Materials Symposium (MMMS) -- MAR 03-07, 2024 -- Orlando, FL
Keywords: Polymer blends; Polymer composites; Shielding efficiency; Mechanical properties